Jazz jako model twórczości literackiej. „Jazzowa teoria literatury” Julio Cortázara (Gra w klasy) - Kafel, Małgorzata (Przestrzenie Teorii, 2019)
The article is an attempt at analysing the role of the references to jazz music in the Argentinian writer’s most famous novel, which chapters 10–18 provide an interesting example of the use of this kind of music as a means of a whole range of extraliterary meanings. In the article Hopscotch is treated both as a Cortázar’s artistic manifesto and as an example of a work which fulfils its assumptions in the most complete manner. Musical elements such as improvisation and swing shape the novel in its various aspects, from narration to structure, reflecting a surrealism-inspired need to create literature that transcends traditional ontological frameworks. Jazz is also an illustration of aspirations to independence in artistic and social fields, as well as a means of conveying philosophical ideas and reaching the subconscious.